Integrative Taxonomy Of The Genus Barbodes (Cyprinidae) In Peninsular Malaysia With A Focus On The B. Binotatus Species Complex And B. Lateristriga Morphotypes - Sobri, Noor Zahidah Ahmad (2023)
This study focused on the fish genus Barbodes Bleeker, 1859 in Peninsular Malaysia, where four species have been often reported in the literatures, B. binotatus, B. banksi, B. lateristriga and B. dunckeri. Preliminary observations on the Barbodes fishes in Peninsular Malaysia had found variation in body pattern. These variations can not only be seen interspecifically but also be seen intraspecifically, which complicates the taxonomic designation of the species in this region. This is particularly true for two groups of species which are referred to as the (1) “B. binotatus species complex”, which includes three valid species: B. binotatus, B. banksi and B. rhombeus, and (2) “B. lateristriga morphotypes”. This study aims to resolve the taxonomic status of B. binotatus species complex and B. lateristriga morphotypes by morphology and molecular approach and provide a comprehensive species list of genus Barbodes in Peninsular Malaysia. Morphology studies of 106 specimens from different localities indicated three types of Barbodes species found in Peninsular Malaysia: B. binotatus, B. rhombeus and B. banksi referred to their size of black spot at the dorsal-fin base. All of these specimens also compared with the true B. binotatus from Java, holotype of B. rhombeus from Thailand and the true B. banksi from Sarawak respectively. Based on the analysis of morphometric using one-way ANOVA and post-hoc Tukey test, there are 27 characters of morphometric measurements showed significant difference (p<0.05) among the B. binotatus species complex. Investigation on this species complex by PCA and DFA analysis revealed the characters of snout length (SnL), prenostril length (PreNosL), caudal peduncle length (CPL), anal-fin depressed length (ADepL), anal-fin height (AHi) and dorsal-fin height (DHi) as important characters in separation of them.